2016
DOI: 10.1111/jam.13156
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species production, induced by atmospheric modification, alter conidial quality ofBeauveria bassiana

Abstract: This is the first study in which conidial infectivity and ROS production in B. bassiana has been related, enhancing the knowledge of the effect of O2 pulses in B. bassiana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…This differentiation process is preceded by oxidant states in which reactive oxygen species (ROS) accumulate, which lead to the appearance of protein oxidation (Toledo and Hansberg ). In B. bassiana Bb 882·5, a 26% × 2 treatment led to oxidant states in which lipoperoxidation occurred (Garza‐López et al ) and ROS accumulated (Pérez‐Guzmán et al ). However, a headspace volume:gds ratio of 15 ml per gds was used for those experiments, which is more likely to represent stress by hypoxia‐anoxia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This differentiation process is preceded by oxidant states in which reactive oxygen species (ROS) accumulate, which lead to the appearance of protein oxidation (Toledo and Hansberg ). In B. bassiana Bb 882·5, a 26% × 2 treatment led to oxidant states in which lipoperoxidation occurred (Garza‐López et al ) and ROS accumulated (Pérez‐Guzmán et al ). However, a headspace volume:gds ratio of 15 ml per gds was used for those experiments, which is more likely to represent stress by hypoxia‐anoxia.…”
Section: Resultsmentioning
confidence: 99%
“…Hyphal differentiation leading to conidiation is a critical factor for entomopathogenic fungi whose conidia are the infective units for the control of insect plagues (Pérez‐Guzmán et al ). Many variables affect the conidiation process, including the oxygen level in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Second, according to a previous report in C. albicans [2], NDT80 deletion mutants also showed sensitivity to heat stress in B. bassiana. Heat stress could promote cellular ROS generation, thereby damaging certain biomolecules, such as DNA, lipids or proteins [33,36]. Antioxidant enzymes can scavenge diverse intracellular ROS [27,37].…”
Section: Plos Onementioning
confidence: 99%
“…To apply Trichoderma as biopesticide on the field crops is necessary to do it in form of spores because they are the most infective units. It is demonstrated that spores produced by solid-state fermentation (SSF) are more resistant to the real conditions found in nature [9]. SSF is a microbial process carried out on solid materials surface on the absence of free water.…”
Section: Introductionmentioning
confidence: 99%